Hot news: Unveiling long COVID-19 disease - Soriano, Vicente; Ganado-Pinilla, Pilar; Sánchez-Santos, Miguel; Barreiro, Pablo (AIDS Reviews, 2021)
The clinical spectrum of “Severe Acute Respiratory Syndrome Coronavirus type 2” (SARS-CoV-2) infection is wider than initially thought. The coronavirus does not establish a chronic cellular infection, in contrast with HIV or the hepatitis B virus, that keeps their genomes, respectively, as proviruses integrated within the chromosomes or as episomes (Soriano et al. J Antimicrob Chemother 2014).
Keywords: amphotericin B; C reactive protein; haptoglobin; immunoglobulin G; Scopus(2)